STUDENTS’ ABILITY AND DIFFICULTIES IN WRITING REPORT TEXT AT SECOND SEMESTER STUDENTS OF STIE-SAK ACADEMIC YEAR 2024/2025 - Sukarta Kartawijaya; Yelnim; Al-Padli (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research was a descriptive research which used to analyzed students’ ability and difficulties at second semester of accounting major at STIE-SAK academic year 2024/2025. The population of this research was students all the students at second semester of accounting major. The instrument used in this research was writing test. The research findings showed that the students’ ability were low in understanding report text because from the students’ score, there was 1 student got 80, 1 students got 70, 1 student got 60, and most of the students or there were 10 students got under 60. Then, after counting the students’ percentage score, it showed that only a students got A, 1 student got B, C, and D. There were 9 students got E. It could be concluded that the students at second semester of accounting major at STIE-SAK academic year 2024/2025 failed in writing report text. Moreover, in writing report text, the students faced some difficulties. The difficulties were: the understanding of paragraph, the understanding of generic structure, and the understanding of language features.